Social work, law and ethics - Dickens, Jonathan, 1961- (London : Routledge, 2013)
Law and ethics are two vital aspects of social work -- all social workers need to practise according to the law and their codes of ethics and conduct. However, the relationship between the law and social work values and ethics is not without its tensions and this book takes a problem-based approach to explore the dilemmas and challenges that can arise. The first part of the book sets out frameworks for thinking about the law and ethics, and how they relate to social work. It also introduces some of the big philosophical and sociological questions about the purposes of law and of ethics and how they relate to society more generally. In the second part, the book explores a series of areas where profound dilemmas arise -- such as end-of-life decisions, respecting peoples' choices but ensuring their safety and that of others, responsibility and blame, making allowance for different cultural traditions and breaking confidentiality.
Includes bibliographical references and index.
Keywords: Social service; Social workers -- Legal status, laws, etc; Social workers -- Professional ethics